Comparison of a Novel Biodegradable Polymer Sirolimus-Eluting Stent With a Durable Polymer Everolimus-Eluting Stent: Results of the Randomized BIOFLOW-II Trial. (February 2015) - Windecker, Stephan; Haude, Michael; Neumann, Franz-Josef; Stangl, Karl; Witzenbichler, Bernhard; Slagboom, Ton; Sabaté, Manel; Goicolea, Javier; Barragan, Paul; Cook, Stéphane; Piot, Christophe; Richardt, Gert; et al.
Abstract : Background—: Biodegradable polymers for release of antiproliferative drugs from drug-eluting stents aim to improve vascular healing. We assessed noninferiority of a novel ultrathin strut drug-eluting stent releasing sirolimus from a biodegradable polymer (Orsiro, O-SES) compared with the durable polymer Xience Prime everolimus-eluting stent (X-EES) in terms of the primary end point in-stent late lumen loss at 9 months. Methods and Results—: A total of 452 patients were randomly assigned 2:1 to treatment with O-SES (298 patients, 332 lesions) or X-EES (154 patients, 173 lesions) in a multicenter, noninferiority trial. The primary end point was in-stent late loss at 9 months. O-SES was noninferior to X-EES for the primary end point (0.10±0.32 versus 0.11±0.29 mm; difference=0.00063 mm; 95% confidence interval, −0.06 to 0.07; P noninferiority <0.0001). Clinical outcome showed similar rates of target-lesion failure at 1 year (O-SES 6.5% versus X-EES 8.0%; hazard ratio=0.82; 95% confidence interval, 0.40–1.68; log-rank test: P =0.58) without cases of stent thrombosis. A subgroup of patients (n=55) underwent serial optical coherence tomography at 9 months, which demonstrated similar neointimal thickness among lesions allocated to O-SES and X-EES (0.10±0.04 mm versus 0.11±0.04 mm; −0.01 [−0.04, −0.01]; P =0.37). Another subgroup of patients (n=56) underwent serial intravascular ultrasound at baseline and 9 months indicating a potential difference in neointimal area at follow-up (O-SES, 0.16±0.33 mm 2 versus X-EES, 0.43±0.56 mm 2 ; P =0.04). Conclusions—: Compared with durable polymer X-EES, novel biodegradable polymer–based O-SES was found noninferior for the primary end point in-stent late lumen loss at 9 months. Clinical event rates were comparable without cases of stent thrombosis throughout 1 year of follow-up. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01356888.